Effect of RSC Water on Physico-chemical Properties of Typic Haplustalfs with Marigold (Tagetes erecta) and Chrysanthemum (Chrysanthemum spp.) - Garhwal, R S; Totawat, K L; Yadva, B K (Annals of Arid Zone, 2016)
A lysimeter study was carried out in the Department of Agricultural Chemistry and Soil Science at Rajasthan College of Agriculture, Udaipur. The treatments comprized of two texturally different soils (sandy loam and clay loam), four RSC levels (0.0, 2.5, 5.0 and 7.5 m moles L-1) in irrigation water and two flowering annuals (marigold and chrysanthemum) making 16 treatment combinations in factorial completely randomized design in triplicate. The ECe, organic carbon, water soluble Ca2+, Mg2+, K+, Na+, Cl- and SO4- and exchangeable Ca2+, Mg2+, K+ and SAR decreased, while the pH, water soluble CO3- and HCO3-, exchangeable Na+ and ESP increased with rise in RSC level in irrigation water. A significantly low soluble Ca2+, Mg2+ and HCO3- contents and higher values of soluble SO4- and exchangeable K+ were observed in the soil with marigold. A higher accumulation of Mg2+, K+ and exchangeable K+ was recorded in sandy loam soil, while higher values of exchangeable Ca2+, Mg2+ and Na+ were recorded in clay loam soil. Dry matter yield per lysimeter registered a decrease with an increase in RSC levels in irrigation water from 0.0 to 7.5 m moles L-1. The reduction in dry matter yield was more pronounced in clay loam soil as compared to sandy loam soil. The content of N in flowering annuals increased with an increase in the RSC level in irrigation water, whereas the contents of P, K Cu, Fe, Mn and Zn showed a decrease with an increase in RSC levels in irrigation water from 0.0 to 7.5 m moles L-1. Further, a higher content of N, P, Cu, Mn, and Zn was recorded for marigold. Key words: Residual sodium carbonate, marigold, chrysanthemum, nutrient content.